The Implementation of the Picture and Picture Learning Model to Enhance Students’ Motivation and Academic Achievement in Narrative Writing - Raudatul Izmi; Arini Vika Sari (PT. Mifandi Mandiri Digital, 2023)
Language can also be understood as a system of learning that involves communication procedures. In language learning, one essential component is writing skills, which are crucial to develop and practice—particularly in writing narrative essays. A narrative essay is a form of writing that describes events in chronological order. To enhance students' ability to write narrative essays, this study employed the Picture and Picture method, which presents instructional material through a sequence of images integrated with media. This research utilized a Classroom Action Research (CAR) design consisting of two cycles. Data were collected through observation, tests, and documentation. The subjects of this study were 25 seventh-grade students at MTs Alwashliyah Pantai Labu during the 2021/2022 academic year. The aim was to improve their narrative essay writing skills. The results showed a significant improvement in students’ writing performance, with the average score increasing from 67.2 before the implementation of the method to 81.6 afterward. These findings indicate that the Picture and Picture method is more effective in enhancing students’ writing skills compared to the previously used lecture-based approach.